Colloidal synthesis of wurtz-stannite Cu2CdGeS4 nanocrystals with high catalytic activity toward iodine redox couples in dye-sensitized solar cells. Issue 72 (15th August 2016) - Huang, Shoushuang; Zai, Jiantao; Ma, Dui; He, Qingquan; Liu, Yuanyuan; Qiao, Qiquan; Qian, Xuefeng
Abstract : Wurtz-stannite Cu2 CdGeS4 nanocrystals were synthesized via a facile hot-injection method at a low temperature. Abstract : Wurtz-stannite Cu2 CdGeS4 nanocrystals were synthesized via a facile hot-injection method at a low temperature. They exhibited low charge transfer resistance at the electrolyte–electrode interface and high electrocatalytic activity for the reduction of I3 − in dye-sensitized solar cells (DSSCs). Moreover, this DSSC showed a power conversion efficiency of 7.67%, comparable to the Pt-based device (7.54%).